Multimodality coronary imaging to predict non-culprit territory unrecognized myocardial infarction assessed by cardiac magnetic resonance in non-ST-elevation acute coronary syndrome. (3rd October 2022) - Hoshino, M; Sugiyama, T; Kanaji, Y; Hada, M; Misawa, T; Nagamine, T; Ueno, H; Matsuda, K; Sayama, K; Yonetsu, T; Sasano, T; Kakuta, T
Abstract: Objectives: This study sought to assess the predictors of coherence tomography (OCT) and coronary computed tomography angiographic (CCTA) findings for non-infarct-related (non-IR) territory unrecognized myocardial infarction (UMI) in patients with first non-ST-elevation acute coronary syndrome (NSTE-ACS) presentation. Background: UMI detected by cardiac magnetic resonance (CMR) is associated with adverse outcomes in patients with both acute coronary syndrome and chronic coronary syndrome. However, the association between the presence of UMI and findings of multimodality coronary imaging remains unknown. Methods: We investigated 69 patients with a first clinical episode of NSTE-ACS, who underwent pre-PCI 320-slice CCTA, uncomplicated urgent percutaneous coronary intervention (PCI) with OCT assessment within 48 hours of admission, and post-PCI CMR. UMI was assessed on late gadolinium enhancement (LGE-CMR) by identifying regions of hyperenhancement with an ischemic distribution pattern in non-IR territories (non-IR UMI). Results: Non-IR UMI was detected in 11 patients (15.9%). ROC analysis revealed the optimal cut-off value of PCATA in culprit vessel for predicting the presence of non-IR UMI were −71.3. Lower ejection fraction, higher Gensini score, high pericoronary inflammation (>−71.3), OCT-defined culprit lesion plaque rupture (OCT-PR), and OCT-defined culprit lesion cholesterol crystal (OCT-CC) were significantly associated with the presence of non-IR UMI (Figure 1A). OCT findings are shown in Figure 1B. Patients with non-IR UMI had a higher prevalence of OCT-PR and OCT-CC than those without. Compared with patients without non-IR UMI, the prevalence of high pericoronary inflammation was higher in patients with non-IR UMI (Figure 1C). When the total cohort was divided into four groups according to the numbers of aforementioned OCT-derived risk factors and PCATA, patients with all of these UMI risk factors showed 46.2% (6/13) prevalence of non-IR UMI, whereas none of 15 patients without these factors showed non-IR UMI (Figure 1D). Conclusions: When culprit lesion showed OCT-PR, OCT-CC, and high PCATA, about half of these patients are likely to have non-IR UMI. The integrated CCTA and OCT assessment may help identify the presence of non-IR UMI, potentially providing prognostic information in first NSTE-ACS patients. Funding Acknowledgement: Type of funding sources: None.